A Road Through Pakistan, and What This Means for India. Issue 3 (4th May 2019) - Zaidi, S. Akbar
ABSTRACT: Pakistan's largest donor has been the United States of America, granting around $ 70 bn in aid. In 2015, China, as part of its One Belt One Road global ambitions, promised Pakistan $ 46 bn (since revised to $ 60 bn), for a road running from its border to the port of Gwadar. The China Pakistan Economic Corridor (CPEC), is being seen as a 'fate-changer' for Pakistan. CPEC could change Pakistan's fate in more ways than one; this article explores the domestic and regional consequences of China's involvement in Pakistan, and what this will mean for South Asia and for India.